LITERATURE REVIEW: EVALUASI RAGAM METODE PERAWATAN PADA PASIEN HIV/AIDS - Suarnianti; Muh. Athal Aftal Sofhyan; Nur Khalid (Nursing Arts, 2020)
ABSTRACT According to WHO data, there are 36.9 million people living with HIV / AIDS worldwide. New HIV / AIDS infections worldwide in 2017 reached 1.8 million people. Although there is no drug that can kill the virus that causes AIDS, HIV infection and replication can still be prevented with treatment that can increase the hope and quality of life of patients by administering a combination of antiretroviral drugs. One way to help manage problems that make you feel depressed / stressed so as not to have a negative impact on your health is through psychosocial treatment with the Spiritual Emotional Freedom Technique method and social support methods. This literature review is through searching the results of scientific publications in the period 2016-2020 using the pubmed and google scholar databases with keywords (ARV) and HIV / AIDS, (social support) and HIV / AIDS, and (Spiritual Emotional Technique Freedom) and HIV / AIDS. Search for articles related to 9 sources included in the criteria. The conclusion was that three of these methods are equally effective in the treatment of people living with HIV in improving the health status and quality of life for people living with HIV. Keywords: ARV; social support; spiritual emotional technique freedom ABSTRAK Menurut data WHO terdapat 36,9 juta orang hidup dengan HIV/AIDS diseluruh dunia. Infeksi baru HIV/AIDS di seluruh dunia pada 2017 mencapai 1,8 juta orang. Meskipun belum ada obat yang dapat membunuh virus penyebab AIDS, namun infeksi dan replikasi HIV masih bisa dicegah dengan pengobatan yang mampu meningkatkan harapan dan kualitas hidup pasiennya dengan pemberian kombinasi obat-obat antiretroviral. Salah satu cara untuk membantu pengelolaan masalah yang membuat perasaan tertekan/stres agar tidak membawa pengaruh negatif terhadap kesehatannya adalah melalui perawatan psikososial dengan metode Spiritual Emotional Freedom Technique dan metode sosial support. Tinjauan litrerature review ini melalui penelusuran hasil-hasil publikasi ilmiah pada rentang tahun 2016-2020 menggunakan database pubmed dan google scholar dengan kata kunci (ARV) and HIV/AIDS, (social support) and HIV/AIDS, dan (Spiritual Emotional Technique Freedom) and HIV/AIDS. Penelusuran artikel yang terkait 9 sumber yang termasuk dalam kriteria. Kesimpulannya adalah ketiga metode ini sama-sama efektif dalam perawatan ODHA dalam memperbaiki status kesehatan dan kualitas hidup bagi ODHA.